Criminal Liability Analysis of Healthcare Professionals in Malpractice Cases Based on Digital Evidence in the Era of Electronic Medical Records - Faisal Lutfi; Sumarno Sumarno; Mhd. Azhali Siregar (Journal Evidence Of Law, 2026)
The digitalization of healthcare services through the implementation of Electronic Medical Records (EMR) has important legal implications for proving medical malpractice cases. This study aims to analyze the construction of criminal liability for healthcare workers in malpractice cases using EMR-based digital evidence, as well as assess the strength of the evidence and its legal implications in the Indonesian criminal justice system. The method used is normative juridical research with a statutory, conceptual, and analytical approach to related doctrines and decisions. The results show that the criminal liability of healthcare workers remains based on the principles of actus reus and mens rea, with an emphasis on proving the element of fault in the form of intent or negligence. EMR as an electronic document is recognized as valid evidence under the Health Law No. 17 of 2023, Law No. 1 of 2024 as the Second Amendment to Law No. 11 of 2008 concerning Electronic Information and Transactions, and derivative regulations, but its evidentiary strength is highly dependent on the fulfillment of the principles of data authentication, integrity, and validity. The findings also indicate that the use of EMR-based digital evidence has the potential to strengthen the proof of fault through digital forensic support, while also raising challenges related to personal data protection and the risk of criminalization of healthcare workers. This study concludes that harmonization of regulations and technical guidelines for digital evidence is necessary so that EMR can function optimally as evidence that ensures legal certainty, substantive justice, and balanced legal protection for patients and healthcare professionals.